Characterization of blaNDM-5-harbouring Klebsiella pneumoniae sequence type 11 international high-risk clones isolated from clinical samples in Yangon General Hospital, a tertiary-care hospital in Myanmar. Issue 5 (26th May 2021) - Sugawara, Yo; Akeda, Yukihiro; Hagiya, Hideharu; Zin, Khwar Nyo; Aye, Mya Mya; Takeuchi, Dan; Matsumoto, Yuki; Motooka, Daisuke; Nishi, Isao; Tomono, Kazunori; Hamada, Shigeyuki
Abstract : Fifteen Klebsiella pneumoniae isolates harbouring bla NDM genes were identified from blood and sputum specimens of patients at a tertiary-care facility (Yangon General Hospital, Yangon, Myanmar) in 2018. Two of the isolates belonged to sequence type (ST) 11, an international high-risk clone. Whole-genome sequencing and phylogenetic analyses revealed that these two isolates were clustered together with other ST11 isolates originating from other countries. The isolates harboured the bla NDM-5 gene on an IncFII-type plasmid that is prevalent among carbapenemase-producing Enterobacteriaceae in Yangon but has rarely been found in other ST11 isolates. Our data suggests the regional presence of the ST11 international high-risk clone and its acquisition of an endemic bla NDM-5 -carrying plasmid.